(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2020)
The study aimed to examine the effect of the alcoholic extract of the flaxseed on naphthalene-induced hepatotoxicity in the Syrian hamsters and to identify some of the resulted biochemical and histological changes. This study has been conducted on 32 hamster in the four equal groups. The animals of the first group (control) / the group I / have been immunized with the physiological solution NACL at a concentration of (0.9%). However, the second group / the group II/ have been extracted with the alcoholic extract of the flaxseed only in dose of (30 mg / 100 g) once daily for three weeks. also, the third group/ the group III/ have been dosed with naphthalene (100 mg / 100 g) daily for three weeks, the Group IV have been administered simultaneously with the alcoholic extract of the flaxseed and naphthalene at the same level in terms of the dose and treatment duration. The results of the biochemical study showed a significant increase (P <0.001) in the concentrations of the liver enzyme (ALT, AST) in the serum related to the third group in comparison with the control and the second groups. However, there has been a significant decrease (P <0.001) in the concentrations of the two enzymes in the serum related to the group IV compared with the group III. The results of the histological study of the livers of the / group III / third group animals have showed a clear appearance of some signs of necrosis, a decline in the cell membranes and the disappearance of their nuclei with a severe vascular congestion, especially in the portal distances within the hepatic tissue, congestion, expansion of the central veins, hepatocytosis, poor coloration and Inflammatory infiltration of the white blood cells from the neutrophils and lymphocytes. The improvement was evident through the signs of restoration and increased Kupffer cells in the tissue of the animal livers which were dosed with the alcoholic extract of the flaxseed and naphthalene .The results show the importance of the flaxseed and its extracts as a natural substance in the prevention of hepatotoxicity with naphthalene. هدفت الدراسة إلى اختبار تأثير المستخلص الكحولي لبذور الكتان في التسمم الكبدي المستحدث بمادة النفتالين في الهامستر السوري ، وتحديد بعض التغيرات الكيميائية الحيوية والنسيجية نتيجة ذلك. أُجريت الدراسة على 32 هامستر في أربع مجموعات متساوية ، جُرعت حيوانات المجموعة الأولى (الشاهدة) بالمحلول الفيزيولوجي NACL (بتركيز0.9%) ، وجُرعت المجموعة الثانية بالمستخلص الكحولي لبذور الكتان فقط بجرعة مقدارها(30ملغ/100غ) لمرة واحدة يومياً ولمدة ثلاثة أسابيع ، كما جُرعت المجموعة الثالثة بمادة النفتالين بمقدار(100ملغ/100غ) يومياً لمدة ثلاثة أسابيع، أما المجموعة الرابعة فقد جُرعت بالمستخلص الكحولي لبذور الكتان والنفتالين بشكل متزامن والمقدار نفسه من الجرعات السابقة ومدة العلاج . أظهرت نتائج الدراسة الحيوية الكيميائية ارتفاعاً معنوياً P<0.001)) في تراكيز أنزيمي الكبد (ALT,AST) في مصل دم المجموعة الثالثة مقارنة مع المجموعتين الشاهدة والثانية. في حين سُجل انخفاض معنويP<0.001)) لتراكيز الأنزيمين في مصل دم المجموعة الرابعة مقارنة مع المجموعة الثالثة . لقد أوضحت نتائج الدراسة النسيجية لأكباد حيوانات المجموعة الثالثة ظهور واضح لبعض علامات التنخر وتخرب الأغشية الخلوية واختفاء أنويتها مع احتقان وعائي شديد وخاصة في المسافات البابية ضمن النسيج الكبدي واحتقان وتوسع في الأوردة المركزية وانتباج الخلايا الكبدية وضعف تلونها وارتشاح التهابي لخلايا الدم البيض من عدلات وليمفاويات ، بينما ظهر التحسن واضحاً من خلال علامات الترميم وزيادة خلايا كوبفر في أنسجة أكباد الحيوانات التي جُرعت بالمستخلص الكحولي لبذور الكتان والنفتالين معاً . تظهر النتائج الأهمية الكبيرة لبذور الكتان ومستخلصاتها كمادة طبيعية في الوقاية من التسمم الكبدي بمادة النفتالين .